Self-injection of kerosene with chemical pneumonitis and abscess formation ‒ a case report and literature review - Wijesinghe, Anura; Rathnasekara, Thilina; Sewwandi, Hashini; Weerawansa, Prasanna; Siribaddana, Sisira (Rzeszów University Press, 2025)
Introduction and aim. Kerosene, a widely available household fuel in Sri Lanka, is a common cause of accidental poisoning, especially in children, and is occasionally used for self-harm, which can cause complications such as chemical pneumonitis, abscesses, and thrombosis. Its unsafe storage practices increase the risk of accidental exposure. Description of the case. A 16-year-old Sri Lankan male self-injected kerosene into the left cubital fossa. Although initially stable, he later developed chemical pneumonitis, left cephalic vein thrombosis, and a sterile abscess at the injection site. Conclusion. Early multidisciplinary intervention and close clinical monitoring led to a favorable outcome. A review of the literature reveals that intravenous hydrocarbon injection, although rare, can lead to significant local and systemic toxicities.
Informed written consent has been obtained from the patient’s mother, and ethics approval is not applicable for this manuscript.
Keywords: abscess; kerosene; pneumonitis; self-injection